Habilidades práxicas orofaciais, alterações do sistema estomatognático e tipos de alterações de fala de crianças com desvios fonético e fonológico - Bertagnolli, Ana Paula Coitino (2012)
Objective: The objectives of this essay are to verify the orofacial praxis skills, alterations of the stomatognathic system (SEG) and the characteristics in the SEG of children with typical phonological development (DFT), with phonetic-phonological disorder (DFoFe) and phonological disorder (DF), correlating these features with the types of speech errors (phonological processes) that they present. Method: The sample was consisted of 19 subjects that were diagnosed with DF, belonging to the corpus of Marini (2010), plus 10 individuals with the same diagnosis, reaching a total of 29 subjects with DF, 29 subjects with DFT, and also the sample of Marini (2010). Still, 24 subjects diagnosed with DFoFe made part of the corpus. Two tests of praxis skills the Orofacial Praxis Test (Berzoatti,Tavano e Fabbro, 2007) and the Bucofacial Articulatory Praxis test (Hage, 2000) were applied; and also was applied the evaluation of the stomatognathic system and the Child Phonological Evaluation (Yavas,Hernandorena e Lamprecht, 1991). The statistical treatment was performed making use of the chi-squared, Mann-Whitney and Kruskal-Wallis. Results: Those children with DFoFe obtained the worse performance on the praxis tests, major changes in the stomatognathic system, and presented distortions in the phonemes /s/ and /z/.The repaired strategies most commonly performed by all subjects in this study were fricative devoicing, gliding; cluster reduction; the praxis alteration and changes in stomatognathic system had influence in these repaired strategies of plosive devoicing, cluster reduction and lisp. Conclusion: Children with DFoFe present greater discrepancy in orofacial praxis skills and major changes in the SEG, while the other two groups analyzed displayed minor changes in these variables. The praxis skills as well as the changes of OFA influenced in the making of the phonological processes performed by these subjects.